Immigration enforcement policies and the mental health of US-citizens: findings from a comparative analysis - Pinedo, Miguel (Am J Community Psychol, 2020)
We examined the differential impact of having a family member, friend, or co-worker/community member detained or deported on the mental health of US citizens. In 2019, a sample of 3,446 adult participants of White, Black, and Latinx racial/ethnic descent were recruited to complete an online questionnaire. Participants completed the Patient Health Questionnaire-4 to screen for anxiety, depression, and psychological distress. Analyses were restricted to US citizens (n = 3,282). Multivariable logistic and linear regressions were conducted to examine the mental health of US citizens who reported personally knowing a migrant who has been detained or deported and by their relationship to the migrant, overall and among Latinxs only. Among US citizens, 32% reported personally knowing someone who has been detained or deported. In multivariable analyses, US citizens who personally knew a detained or deported migrant were more likely to report anxiety, depression, and greater psychological distress. Associations were more pronounced among those who reported having a family member detained or deported. US-citizen Latinxs with social ties to migrants who have been detained or deported were especially more likely to report poor mental health than White and Latinx participants who did not personally know a migrant who has been detained or deported. It is critical that policy makers consider the potential mental health harms on migrants and it’s own citizens when designing policies targeting migrant communities.